ANALISA HUBUNGAN TINDAKAN SUPERVISI DAN BUDAYA ORGANISASI TERHADAP KINERJA INDIVIDUAL AKUNTAN YUNIOR DI KANTOR AKUNTAN PUBLIK DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - MURTANTO; MELVA DJASMIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
The objective of this research is to analyze the impact of supervisory action, organizational culture, job satisfaction and invidual performance junior accountants in public accounting firms. Data for the research were collected in two ways, by contact persons and direct survey to respondents. This study reports the results of a survey of 276 junior accountants from 17 small public accounting firns and 6 big public accounting firms. Purposive method is used to define the sample. The correlational,t-test and SEM Techniques was used to develop theoritical model and analyze the data. This study find that the two major elements for supervisory action recommended by the AECC: leadership and mentoring, and assignments, do not give impact on the job satisfaction. Working conditions give impact on the job satisfaction but job satisfaction do not give impact on the individual performance. This study also find that the three element of organizational culture, bureaucratic and innovative culture were negatively correlated but do not give impact on the job satisfaction. Unexpectedly, supportive culture was positively correlated but do not give impact on the job satisfaction. However, there are no significant differences between small and big public accounting firms for the supervisory actions and job satisfaction. But there are significant differences for the individual performance.